The Level of Peace and Order Amid Pandemic at Barangay San. Bartolome in Novaliches Quezon City: Vol. 3, No. 1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers used a quantitative method to collect information from existing and potential respondents by sending questionnaires. The researcher interviewed barangay officials and tanods. The main instrument used to gather information is to answer the specific problem raised in every question included in the questionnaires. Based on the data gathered, strategies, techniques, equipment, and officials for peace and order amid the pandemic were assessed as “effective. Also, various problems were encountered by respondents to their tasks and responsibilities in peace and order during the pandemic. However, most problems encountered were assessed as “moderately agree” except for the lack of CCTV cameras installed. All of the proposed measures to improve peace and order were assessed as “recommended.” The findings of this study can be used to craft a guide to improve the implementation and promotion of peace and order amid the COVID-19 pandemic.The researchers recommend that barangay officials should involve the citizens in promoting peace and order and consider some of the measures proposed to improve the implementation of peace and order amid the COVID-19 pandemic and that citizens should be more aware of the policies and ordinances implemented to promote peace and order on their respective areas.